Predictive Value of Preoperative Positive Urine Cytology for Development of Bladder Cancer After Nephroureterectomy in Patients With Upper Urinary Tract Urothelial Carcinoma: A Prognostic Nomogram Based on a Retrospective Multicenter Cohort Study and Systematic Meta-Analysis - Fan, Bo; Huang, Yuanbin; Wen, Shuang; Teng, Qiliang; Yang, Xinrui; Sun, Man; Chen, Tingyu; Huang, Yan; Wang, Yumei; Liu, Zhiyu (Frontiers in Oncology, 2021)
Background: Upper urinary tract urothelial carcinoma (UUT-UC) is a rare and severe urinary malignancy. Several studies have explored the relationship between preoperative urine cytology and intravesical recurrence (IVR) in patients with UUT-UC. However, the results of these studies are controversial or even contradictory, and investigations with UUT-UC patients in Northeast China are rare. Methods: We first estimated the prognostic significance of preoperative urine cytology in the outcomes of intravesical recurrence in 231 UUT-UC patients (training cohort=142, validation cohort=89) after radical nephroureterectomy (RNU) by nomogram model. Subsequently, we quantitatively combined our results with the published data after searching several databases to assess whether preoperative positive urine cytology was associated with poor intravesical recurrence-free survival and a high risk of tumor malignant biological behavior. Results: Firstly, the multicenter retrospective cohort study demonstrated that preoperative positive urine cytology correlated with poor intravesical recurrence-free survival and can be served as significant independent predictors of IVR by Kaplan-meier curves, and Cox-regression analysis. The construction of the nomogram demonstrated that the predictive efficacy and accuracy were significantly improved when preoperative urine cytology was combined. Meanwhile, meta-analysis showed that preoperative positive urine cytology was associated with a 49% increased risk of IVR. In the subgroup analysis by region, study type, and sample size, the pooled HRs were statistically significant for the Japan subgroup (HR 1.32), China subgroup (HR 1.88), cohort study subgroup (HR 1.45), and the single arm study subgroup (HR 1.63). Conclusions: Preoperative urine cytology was validated as a potential predictor of intravesical recurrence in patients with UUT-UC after RNU, although these results need to be generalized with caution. Large, prospective trials are required to further confirm its significance in prognosis and tumor malignant biological behaviour.